Demystifying adipogenesis : role of microenvironment in stem cell differentiation - Guneta, Vipra (2016)
Tissue regeneration and repair in the body occurs with a well-orchestrated process involving the cells, the extracellular matrix (ECM) and the soluble factors. However, the translation of stem cell-based therapies from bench-to-bedside is limited due to the use of xenogenic media components in stem cell culture. These components are prone to batch-to-batch variation and high cost. As it has been found that microenvironmental cues such as the physical environment, topography and physiological conditions affect the differentiation of stem cells, the roles of these cues individually and in combination for triggering adipogenic differentiation of adipose-derived stem cells (ASCs) in vitro was explored in this thesis. In order to accomplish this objective, firstly it was imperative to understand the native adipose tissue microenvironment. Hence, a study involving the characterization of the ASCs and the adipose tissue ECM was first conducted. In addition, the ASCs were compared to the well-established bone marrow-derived mesenchymal stem cells (Bm-MSCs). Even though the two cell populations have similar stem cell properties, they were found to have different predisposition to the osteogenic and adipogenic lineages in vitro. When cultured in similar microenvironments, the cells behaved differently and hence, these inherent differences can be attributed to their native tissue microenvironments. Subsequently, to understand the role of the native microenvironment, ASCs isolated from adipose tissues from two different locations in the body were compared in terms of their stem cell properties and differentiation potential in vitro. From the results, it was found that the abdominal fat ASCs (AF_ASCs) had a stable proliferative profile, whereas breast fat ASCs (BF_ASCs) had a higher self-renewal potential. Also, the AF_ASCs and BF_ASCs had a predisposition to the adipogenic and osteogenic lineages, respectively. These dissimilarities imply that the same populations of cells from the same type of tissue have inherently different properties depending on their location in the body. Subsequently, the ASCs were cultured in vitro on tissue culture plastic (TCP) and the ECM components secreted by these cells in the undifferentiated, osteo-differentiated and adipo-differentiated states were characterized. Extensive characterization of the native adipose tissue ECM was also carried out and these ECM components were then used as a coating for cellular studies with undifferentiated ASCs. The ECM components on their own were shown to have supported initial differentiation, but not terminal differentiation of the ASCs into adipocytes. This highlights the need for other microenvironmental cues that are absent in two-dimensional (2D) in vitro conditions. Platforms that incorporate such cues were subsequently developed using biomaterials such as polydimethylsiloxane (PDMS) and alginate. Factors such as stiffness, surface properties, patterns and topography are investigated for their role in adipogenic differentiation of ASCs. On its own, PDMS is a highly hydrophobic material that requires a surface modification for supporting ASC culture. Therefore, the surface modification of PDMS was optimized using physical and chemical methods without the use of any ECM coating. Treatment of PDMS substrates with plasma oxidation followed by dip coating in poly (vinyl) alcohol was successful in improving the surface properties of PDMS and supporting ASC cell culture. This method was subsequently used in combination with masks that allow for patterned surface modification formation on the PDMS surface. These cues together will provide for the adhesion and alteration of the cell shape, such that adipogenesis is triggered by the PDMS surface itself. In the case of a three dimensional (3D) microenvironment, it was found that alginate scaffolds with lower stiffness, higher porosity and bigger pore sizes favored adipogenesis, whilst the opposite was true for osteogenesis of ASCs. Taken together, a combination of the different pro-adipogenic microenvironmental cues can thus be used for development of platforms that trigger the adipogenesis of ASCs in vitro without the use of xenogenic biological supplements.